Positive electrode material, positive electrode plate containing positive electrode material and lithium ion battery
By preparing the lithium -rich manganese -based materials with a hollow structure, the problem of voltage and capacity attenuation caused by the structural transformation caused by the existing materials during the cycle, and realized the performance of lithium -ion battery with high capacity and long life.
Patent Information
- Application Number
- CN202411856827.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-01-21
AI Technical Summary
There is an irreversible structural change in existing lithium-rich manganese-based materials during the cycle, resulting in a continuous attenuation of discharge voltage and capacity, which cannot meet the needs of high energy density and long life.
By preparing ellipsoidal particles or spherical particles with a hollow structure or a hollow structure with micronuclei as cathode materials, the specific steps include mixing manganese salts and nickel salts with complexing agents and co-precipitating agents, aging and roasting to obtain Lithium-rich manganese-based materials.
This method not only improves the capacity and voltage characteristics of lithium -rich manganese -based materials, but also significantly increases its capacity maintenance rate, which can better apply lithium ion batteries.
Smart Images

Figure CN119340386A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of battery materials, and in particular to a positive electrode material and a positive electrode sheet and a lithium-ion battery containing the same. Background Art
[0002] Lithium-ion batteries (LIBs) are in a leading position in the field of new energy materials due to their high discharge capacity, wide operating temperature range, excellent cycle stability, portability and environmental friendliness. The development of lithium-ion battery technology, on the one hand, can reduce the development and utilization of non-renewable resources such as oil and coal; on the other hand, it continuously accelerates the development and utilization of new energy and clean energy.
[0003] Among the components of lithium-ion batteries, the positive electrode material determines the performance of lithium-ion batteries. The current mainstream positive electrode materials are lithium iron phosphate (LiFePO 4 , LFP), and lithium nickel cobalt manganese oxide (LiNi 1-x-y Mn x Co y O 2 , NCM) and lithium nickel cobalt aluminum oxide (LiNi 1-x-y Al x Co y O 2 , NCA) and other layered positive electrode materials. Among them, LFP has the advantages of large capacity, low price, high safety performance and good thermal stability. However, low conductivity, low actual capacity and high and low temperature performance attenuation make LFP unable to meet the needs of the rapidly developing hybrid vehicles and electric vehicles. NCM and NCA can increase the theoretical capacity by increasing the nickel content. However, as the Ni content increases, the cations become disordered and oxygen is released, resulting in structural and thermal instability.
[0004] In recent years, with the increasing demand for energy density, lithium-rich manganese-based materials (LR) have attracted increasing attention due to their high capacity (>250mAh / g) and high voltage (>4.5 V). However, compared with traditional cathode materials, oxygen vacancies generated by the loss of oxygen can lead to an irreversible structural transformation of LR from the outside to the inside. This is specifically manifested in the rate difference of the first charge and discharge process and the continuous attenuation of discharge voltage and capacity during the cycle. Therefore, a method for modifying LR is urgently needed to enable it to be better used in lithium-ion batteries. Summary of the invention
[0005] The present disclosure provides a positive electrode material, a positive electrode plate and a lithium-ion battery comprising the same, so as to solve the deficiencies in the related art.
[0006] According to a first aspect of an embodiment of the present disclosure, a positive electrode material is provided, wherein the positive electrode material comprises a lithium-rich manganese-based material, wherein the lithium-rich manganese-based material is an aggregate of primary particles; the minor axis length of the primary particles is selected from 190-310 nm, and the major axis length of the primary particles is selected from 400-660 nm; the D90 particle size of the aggregate is selected from 3.75-5.75 μm; and; based on the total mass of the lithium-rich manganese-based material, the mass percentage of lithium element in the lithium-rich manganese-based material is selected from 7.0%-10.0%, and the mass percentage of manganese element in the lithium-rich manganese-based material is selected from 30.5%-37.5%.
[0007] In one aspect of the embodiments of the present disclosure, the lithium-rich manganese-based material further comprises nickel element, and based on the total mass of the lithium-rich manganese-based material, the mass percentage of the nickel element in the lithium-rich manganese-based material is selected from 21.3%-27.3%.
[0008] In one aspect of an embodiment of the present disclosure, in the lithium-rich manganese-based material, the molar ratio of manganese element to nickel element is selected from (1.19-1.88):1.
[0009] In one aspect of an embodiment of the present disclosure, in the lithium-rich manganese-based material, the molar ratio of manganese element to lithium element is selected from (0.38-0.68):1.
[0010] In one aspect of the embodiments of the present disclosure, based on the total mass of the lithium-rich manganese-based material, the percentage content of the sum of the mass of the nickel element and the manganese element in the lithium-rich manganese-based material is selected from 54.85% to 61.35%.
[0011] In one aspect of the disclosed embodiments, the D50 particle size of the aggregates is selected from 2.25-3.50 μm.
[0012] In one aspect of the disclosed embodiments, the D10 particle size of the aggregates is selected from 1.5-2.25 μm.
[0013] In one aspect of the embodiments of the present disclosure, the D100 particle size of the aggregate is less than or equal to 12.01 μm.
[0014] In one aspect of the embodiments of the present disclosure, the lithium-rich manganese-based material is prepared by the following steps: Step 1: dissolving manganese salt and nickel salt in water, adding an aqueous solution of a complexing agent and a coprecipitant under stirring, then heating to 65°C-75°C, continuing stirring for 2-5 hours, and obtaining a precursor after aging; Step 2: Mechanically mixing the precursor and the lithium salt to obtain a mixture; Step 3: calcining the mixture at 450°C-600°C for 3-5h to obtain the lithium-rich manganese-based material.
[0015] In one aspect of the embodiments of the present disclosure, step 1 comprises: dissolving manganese salt and nickel salt in water, adding 55%-65% of the total mass of the complexing agent at room temperature under stirring, then stirring for 15-30 minutes, then heating to 50°C-55°C, adding an aqueous solution of the coprecipitant and the remaining complexing agent, then stirring for 25-45 minutes, further heating to 65°C-75°C, continuing stirring for 2-5 hours, and obtaining a precursor after aging.
[0016] Preferably, step 1 comprises: dissolving manganese salt and nickel salt in water, adding 58%-62% of the total mass of the complexing agent at room temperature under stirring, stirring for 15-30 minutes, then heating to 50°C-55°C, adding an aqueous solution of the coprecipitant and the remaining complexing agent, then stirring for 25-45 minutes, further heating to 65°C-75°C, continuing stirring for 2-5 hours, and obtaining a precursor after aging.
[0017] In one aspect of the embodiments of the present disclosure, the manganese salt is selected from manganese sulfate.
[0018] In one aspect of the embodiments of the present disclosure, the nickel salt is selected from nickel sulfate.
[0019] In one aspect of the embodiments of the present disclosure, when the manganese salt is selected from manganese sulfate and the nickel salt is selected from nickel sulfate, the mass ratio of manganese sulfate to nickel sulfate is selected from (1.16-1.84):1.
[0020] In one aspect of the embodiments of the present disclosure, the complexing agent is selected from ammonia water.
[0021] In one aspect of the embodiments of the present disclosure, when the manganese salt is selected from manganese sulfate and the complexing agent is selected from ammonia water, the mass ratio of ammonia water to manganese sulfate is selected from (0.65-0.85):1.
[0022] In one aspect of the embodiments of the present disclosure, the coprecipitant is selected from at least one of sodium hydroxide, ammonium bicarbonate, sodium bicarbonate, ammonium oxalate and sodium oxalate.
[0023] In one aspect of the embodiments of the present disclosure, when the coprecipitant is selected from sodium hydroxide, the aqueous solution of the coprecipitant is selected from 0.3-0.6 mol / L.
[0024] In one aspect of the embodiments of the present disclosure, when the manganese salt is selected from manganese sulfate and the coprecipitant is selected from sodium hydroxide, the mass ratio of the sodium hydroxide to manganese sulfate is selected from (0.15-0.28):1.
[0025] In one aspect of the embodiments of the present disclosure, when the complexing agent is selected from ammonia water and the coprecipitant is selected from sodium hydroxide, 55%-65% of the total mass of ammonia water is added first, then stirred for 15-30 minutes, and then the sodium hydroxide aqueous solution and the remaining ammonia water are added.
[0026] In one aspect of the embodiments of the present disclosure, the lithium salt is selected from lithium carbonate.
[0027] In one aspect of the embodiments of the present disclosure, when the lithium salt is selected from lithium carbonate and the manganese salt is selected from manganese sulfate, the mass ratio of manganese sulfate to lithium carbonate is selected from (1.52-2.80): In one aspect of the disclosed embodiment, in step 1, the stirring rate is selected from 3000-3800 r / min.
[0028] In one aspect of the embodiments of the present disclosure, the aforementioned lithium-rich manganese-based material is an ellipsoidal particle or a spherical particle having a hollow structure or a hollow structure with a microcore, the wall thickness of the ellipsoidal particle or the spherical particle is 0.33-0.83 μm, and the diameter of the inner wall of the ellipsoidal particle or the spherical particle is 0.43-1.1 μm.
[0029] In one aspect of the embodiments of the present disclosure, the lithium-rich manganese-based material has a thickness greater than or equal to 1.10 m 2 / g specific surface area.
[0030] In one aspect of the embodiments of the present disclosure, the lithium-rich manganese-based material has a mass greater than or equal to 1.40 g / m 3 The tap density.
[0031] According to a second aspect of an embodiment of the present disclosure, a positive electrode plate is provided, the positive electrode plate comprising a positive electrode current collector and a positive electrode material layer coated on the positive electrode current collector, the positive electrode material layer comprising the aforementioned positive electrode material.
[0032] According to a third aspect of the embodiments of the present disclosure, a lithium-ion battery is provided, comprising a negative electrode plate, an electrolyte, a separator and the positive electrode plate mentioned above.
[0033] According to a fourth aspect of an embodiment of the present disclosure, there is provided an electrochemical device, the electrochemical device comprising the aforementioned lithium-ion battery.
[0034] The technical solution provided by the embodiments of the present disclosure may have the following beneficial effects: It can be seen from the above embodiments that the ellipsoidal particles or spherical particles with a hollow structure or a hollow structure with a microcore obtained by the preparation method provided by the present disclosure, when used as a positive electrode material, not only have high capacity and voltage characteristics, but also have excellent capacity retention rate.
[0035] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.
[0037] Figure 1 is a TEM image of the lithium-rich manganese-based material in Example 1.
[0038] Figure 2 is a TEM image of the lithium-rich manganese-based material in Example 6.
[0039] Figure 3 This is the TEM image of the lithium-rich manganese-based material in Comparative Example 1. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.
[0041] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0042] In this article, the terms "comprises", "comprising" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.
[0043] In the description herein, unless otherwise specified, “above” and “below” include the number.
[0044] Unless otherwise specified, the terms used in this disclosure have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this disclosure can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this disclosure).
[0045] The term "about" is used to describe and illustrate small changes. When used in conjunction with an event or situation, the term may refer to an example in which the event or situation occurs precisely and an example in which the event or situation occurs very approximately. For example, when used in conjunction with a numerical value, the term may refer to a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. In addition, amounts, ratios, and other numerical values are sometimes presented in this article in a range format. It should be understood that such a range format is for convenience and simplicity, and should be flexibly understood to include not only numerical values explicitly designated as range limits, but also all individual 10 numerical values or subranges encompassed within the range, as if each numerical value and subrange were explicitly designated.
[0046] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0047] Positive electrode: In some embodiments of the present disclosure, the positive electrode plate involved in the present disclosure includes a positive electrode collector and a positive electrode material layer, the positive electrode material layer is arranged on the surface of the positive electrode collector, and the positive electrode material layer includes a positive electrode material; the positive electrode material contains a lithium-rich manganese-based material, and the lithium-rich manganese-based material is an aggregate of primary particles; the lithium-rich manganese-based material contains lithium, nickel and manganese; and, based on the total mass of the lithium-rich manganese-based material, the mass percentage of the lithium element is selected from 7.0%-10.0%, the mass percentage of the manganese element is selected from 30.5%-37.5%, and the mass percentage of the nickel element is selected from 21.3%-27.3%.
[0048] In some embodiments of the present disclosure, the D100 particle size of the lithium-rich manganese-based material is less than or equal to 12.01 μm, the D90 particle size is selected from 3.75-5.75 μm, the D50 particle size is selected from 2.25-3.50 μm, and the D10 particle size is selected from 1.5-2.25 μm.
[0049] In some embodiments of the present disclosure, the lithium-rich manganese-based material is prepared by the following steps: Step 1: dissolving manganese salt and nickel salt in water, adding an aqueous solution of a complexing agent and a coprecipitant under stirring, then heating to 55°C-60°C, continuing stirring for 2-5 hours, and obtaining a precursor after aging; Step 2: Mechanically mixing the precursor and the lithium salt to obtain a mixture; Step 3: calcining the mixture at 450° C.-600° C. to obtain a lithium-rich manganese-based material.
[0050] In some embodiments of the present disclosure, based on the total mass of the positive electrode sheet, the mass percentage of the positive electrode material is 85%-95%.
[0051] In some embodiments of the present disclosure, the positive electrode material layer further comprises a binder, and the mass percentage of the binder is 0.3%-5% based on the total mass of the positive electrode material layer. In some embodiments of the present disclosure, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.
[0052] In some embodiments of the present disclosure, the positive electrode material layer further includes a conductive agent, and the mass percentage of the conductive agent is 0.3%-3% based on the total mass of the positive electrode material layer. In some embodiments of the present disclosure, the conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive agents include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof, but are not limited thereto.
[0053] In some embodiments of the present disclosure, the positive electrode current collector may be aluminum (Al), but is not limited thereto.
[0054] Negative electrode: In some embodiments of the present disclosure, the lithium-ion battery provided by the present disclosure further includes a negative electrode plate, and the negative electrode plate includes a current collector and a negative electrode material layer disposed on the current collector. The specific types of negative electrode materials are not subject to specific restrictions and can be selected according to needs. Specifically, the negative electrode materials include natural graphite, artificial graphite, mesophase microcarbon beads (abbreviated as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO 2 , spinel-structured lithiated TiO 2 -Li 4 Ti 5 O 12 , Li-Al alloy. Non-limiting examples of carbon materials include crystalline carbon, amorphous carbon and mixtures thereof. Crystalline carbon can be amorphous or flake-shaped, platelet-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.
[0055] In some embodiments of the present disclosure, the negative electrode material layer may include a binder and optionally a conductive material. The binder improves the bonding between the negative electrode material particles and the bonding between the negative electrode material and the current collector.
[0056] In some embodiments of the present disclosure, non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0057] In some embodiments of the present disclosure, the negative electrode material layer includes a conductive agent so that the electrode has conductivity. The conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0058] In some embodiments of the present disclosure, the negative electrode sheet of the present disclosure includes a negative electrode material, a binder and a conductive agent.
[0059] In some embodiments of the present disclosure, the negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0060] Diaphragm: In some embodiments of the present disclosure, the electrochemical device of the present disclosure is provided with a separator between the positive electrode plate and the negative electrode plate to prevent short circuit. The material and shape of the separator used in the electrochemical device of the present disclosure are not particularly limited, and it can be any technology disclosed in the prior art.
[0061] In some embodiments of the present disclosure, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present disclosure.
[0062] In some embodiments of the present disclosure, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide.
[0063] Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0064] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0065] The inorganic layer comprises inorganic particles and a binder, wherein the inorganic particles are selected from one or a combination of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is selected from one or a combination of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.
[0066] The polymer layer contains polymers, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).
[0067] Electrolyte: The lithium-ion batteries and electrochemical devices of the present disclosure also include an electrolyte.
[0068] In some embodiments of the present disclosure, the electrolyte includes a lithium salt and a solvent.
[0069] In some embodiments of the present disclosure, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF 6), lithium tetrafluoroborate (LiBF 4 ), lithium difluorophosphate (LiPO 2 F 2 )、bis(trifluoromethanesulfonyl)imide lithium LiN(CF 3 SO 2 ) 2 (LiTFSI), Lithium Bis(Fluorosulfonyl)imide Li(N(SO 2 F) 2 )(LiFSI)、LiB(C 2 O 4 ) 2 (LiBOB) or lithium difluorooxalatoborate LiBF 2 (C 2 O 4 ) (LiDFOB).
[0070] In some embodiments of the present disclosure, the solvent may be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0071] In some embodiments of the present disclosure, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature performance, etc.
[0072] Lithium-ion battery: In some embodiments of the present disclosure, the lithium-ion battery involved in the present disclosure includes the above-mentioned positive electrode sheet, negative electrode sheet, separator, electrolyte, etc., but is not limited thereto.
[0073] In some embodiments of the present disclosure, the lithium-ion battery involved in the present disclosure may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the lithium-ion battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0074] In some embodiments of the present disclosure, the present disclosure further provides a battery module. The battery module includes the above-mentioned lithium-ion battery. The battery module of the present disclosure uses the above-mentioned lithium-ion battery, and therefore has at least the same advantages as the lithium-ion battery. The number of lithium-ion batteries contained in the battery module of the present disclosure can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0075] In some embodiments of the present disclosure, the present disclosure further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0076] Electrochemical device: In some embodiments of the present disclosure, the electrochemical device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the high power and high energy density requirements of the device for lithium-ion batteries, a battery pack or battery module may be used.
[0077] In other embodiments of the present disclosure, the electrochemical device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be light and thin, and a lithium-ion battery may be used as a power source.
[0078] The present application is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application.
[0079] Embodiment and comparative example: Embodiment 1: Embodiment 1 comprises the following steps: (1) Preparation of lithium-rich manganese-based materials: Dissolve 75g of manganese sulfate and 50g of nickel sulfate in water, add 34.7mL of ammonia water under stirring (3500 r / min), stir at room temperature for 20min, then heat to 57°C, add 23mL of ammonia water and 375mL of 0.5mol / L sodium hydroxide, continue stirring for 35min, then further heat to 70°C, continue stirring for 4h, and obtain the precursor after aging.
[0080] The obtained precursor was mixed with 42 g of lithium carbonate, ball-milled at 500 rpm / min for 4-8 h to obtain a mixture, and then dried; The mixture was taken out and calcined at 550°C for 4 hours to obtain a lithium-rich manganese-based material. The lithium-rich manganese-based material prepared in Example 1 is as follows Figure 1As shown, the lithium-rich manganese-based material is an aggregate of primary particles; the short axis length of the primary particles is 190-310nm, and the long axis length of the primary particles is 400-660nm.
[0081] (2) Preparation of positive electrode sheet: The lithium-rich manganese-based material prepared above, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30 mg / cm 2 After drying at 105℃, cold pressing, punching and welding the pole ears, the positive electrode sheet is obtained.
[0082] (3) Preparation of negative electrode sheet: Artificial graphite, conductive agent SP (conductive carbon black), thickener sodium carboxymethyl cellulose (CMC), and adhesive styrene butadiene rubber (SBR) are fully stirred and mixed in a proper amount of deionized water solvent at a weight ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode material layer, and then cut, slit, and weld the pole ears to obtain a negative electrode sheet.
[0083] (4) Preparation of lithium-ion batteries: The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil aluminum-plastic film, and the above-prepared electrolyte is injected into the dried bare battery cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, the preparation of the lithium battery of Example 1 is completed.
[0084] Embodiment 2: Embodiment 2 comprises the following steps: (1) Preparation of lithium-rich manganese-based materials: Dissolve 75g of manganese sulfate and 50g of nickel sulfate in water, add 28.8mL of ammonia water under stirring (3500 r / min), stir at room temperature for 20min, then heat to 57°C, add 28.9mL of ammonia water and 375mL of 0.5mol / L sodium hydroxide, continue stirring for 35min, then further heat to 70°C, continue stirring for 4h, and obtain the precursor after aging.
[0085] The obtained precursor was mixed with 42 g of lithium carbonate, ball-milled at 500 rpm / min for 4-8 h to obtain a mixture, and then dried; The mixture was taken out and calcined at 550°C for 4 hours to obtain a lithium-rich manganese-based material.
[0086] (2) Preparation of positive electrode sheet: The lithium-rich manganese-based material prepared above, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30 mg / cm 2 After drying at 105℃, cold pressing, punching and welding the pole ears, the positive electrode sheet is obtained.
[0087] (3) Preparation of negative electrode sheet: Artificial graphite, conductive agent SP (conductive carbon black), thickener sodium carboxymethyl cellulose (CMC), and adhesive styrene butadiene rubber (SBR) are fully stirred and mixed in a proper amount of deionized water solvent at a weight ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode material layer, and then cut, slit, and weld the pole ears to obtain a negative electrode sheet.
[0088] (4) Preparation of lithium-ion batteries: The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil aluminum-plastic film, and the above-prepared electrolyte is injected into the dried bare battery cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, the preparation of the lithium battery of Example 2 is completed.
[0089] Embodiment 3: Embodiment 3 comprises the following steps: (1) Preparation of lithium-rich manganese-based materials: Dissolve 75g of manganese sulfate and 50g of nickel sulfate in water, add 40.5mL of ammonia water under stirring (3500 r / min), stir at room temperature for 20min, then heat to 57°C, add 17.2mL of ammonia water and 375mL of 0.5mol / L sodium hydroxide, continue stirring for 35min, then further heat to 70°C, continue stirring for 4h, and obtain the precursor after aging.
[0090] The obtained precursor was mixed with 42 g of lithium carbonate, ball-milled at 500 rpm / min for 4-8 h to obtain a mixture, and then dried; The mixture was taken out and calcined at 550°C for 4 hours to obtain a lithium-rich manganese-based material.
[0091] (2) Preparation of positive electrode sheet: The lithium-rich manganese-based material prepared above, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30 mg / cm 2 After drying at 105℃, cold pressing, punching and welding the pole ears, the positive electrode sheet is obtained.
[0092] (3) Preparation of negative electrode sheet: Artificial graphite, conductive agent SP (conductive carbon black), thickener sodium carboxymethyl cellulose (CMC), and adhesive styrene butadiene rubber (SBR) are fully stirred and mixed in a proper amount of deionized water solvent at a weight ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode material layer, and then cut, slit, and weld the pole ears to obtain a negative electrode sheet.
[0093] (4) Preparation of lithium-ion batteries: The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil aluminum-plastic film, and the above-prepared electrolyte is injected into the dried bare battery cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, the preparation of the lithium battery of Example 3 is completed.
[0094] Embodiment 4: The steps of Example 4 are the same as those of Example 1, except that the mass of nickel sulfate added is 62.5 g instead of 50 g.
[0095] Embodiment 5: The steps of Example 5 are the same as those of Example 1, except that the mass of nickel sulfate added is 41.6 g instead of 50 g.
[0096] Embodiment 6: Embodiment 6 comprises the following steps: (1) Preparation of lithium-rich manganese-based materials: Dissolve 75g of manganese sulfate and 50g of nickel sulfate in water, add 34.7mL of ammonia water under stirring (3500 r / min), stir at room temperature for 20min, then heat to 57°C, add 23mL of ammonia water and 375mL of 0.5mol / L sodium hydroxide, continue stirring for 35min, then further heat to 70°C, continue stirring for 4h, and obtain the precursor after aging.
[0097] The entire precursor was mixed with 28.3 g of lithium carbonate, ball-milled at 500 rpm / min for 4-8 h to obtain a mixture, and dried; The mixture was taken out and calcined at 550°C for 4 hours to obtain a lithium-rich manganese-based material. Figure 2 shown.
[0098] (2) Preparation of positive electrode sheet: The lithium-rich manganese-based material prepared above, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30 mg / cm 2 After drying at 105℃, cold pressing, punching and welding the pole ears, the positive electrode sheet is obtained.
[0099] (3) Preparation of negative electrode sheet: Artificial graphite, conductive agent SP (conductive carbon black), thickener sodium carboxymethyl cellulose (CMC), and adhesive styrene butadiene rubber (SBR) are fully stirred and mixed in a proper amount of deionized water solvent at a weight ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode material layer, and then cut, slit, and weld the pole ears to obtain a negative electrode sheet.
[0100] (4) Preparation of lithium-ion batteries: The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil aluminum-plastic film, and the above-prepared electrolyte is injected into the dried bare battery cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, the preparation of the lithium battery of Example 6 is completed.
[0101] Embodiment 7: Embodiment 7 comprises the following steps: (1) Preparation of lithium-rich manganese-based materials: Dissolve 75g of manganese sulfate and 50g of nickel sulfate in water, add 34.7mL of ammonia water under stirring (3500 r / min), stir at room temperature for 20min, then continue to add 23mL of ammonia water and 375mL of prepared 0.5mol / L sodium hydroxide at room temperature, continue stirring for 35min, then raise the temperature to 70℃, continue stirring for 4h, and obtain the precursor after aging.
[0102] The obtained precursor was mixed with 42 g of lithium carbonate, ball-milled at 500 rpm / min for 4-8 h to obtain a mixture, and then dried; The mixture was taken out and calcined at 550°C for 4 hours to obtain a lithium-rich manganese-based material.
[0103] (2) Preparation of positive electrode sheet: The lithium-rich manganese-based material prepared above, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30 mg / cm 2 After drying at 105℃, cold pressing, punching and welding the pole ears, the positive electrode sheet is obtained.
[0104] (3) Preparation of negative electrode sheet: Artificial graphite, conductive agent SP (conductive carbon black), thickener sodium carboxymethyl cellulose (CMC), and adhesive styrene butadiene rubber (SBR) are fully stirred and mixed in a proper amount of deionized water solvent at a weight ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode material layer, and then cut, slit, and weld the pole ears to obtain a negative electrode sheet.
[0105] (4) Preparation of lithium-ion batteries: The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil aluminum-plastic film, and the above-prepared electrolyte is injected into the dried bare battery cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, the preparation of the lithium battery of Example 7 is completed.
[0106] Comparative Example 1: Comparative Example 1 comprises the following steps: (1) Preparation of lithium-rich manganese-based materials: Dissolve 75g of manganese sulfate and 50g of nickel sulfate in water, add 57.7mL of ammonia water and 375mL of 0.5mol / L sodium hydroxide under stirring (3500 r / min), stir for 55min, then heat to 70°C, continue stirring for 4h, and obtain the precursor after aging.
[0107] The obtained precursor was mixed with 42 g of lithium carbonate, ball-milled at 500 rpm / min for 4-8 h to obtain a mixture, and then dried; The mixture was taken out and calcined at 550° C. for 4 hours to obtain a lithium-rich manganese-based material. Figure 3 As shown. It can be seen that the lithium supplement material prepared in Comparative Example 1 does not have a hollow structure. In the embodiment, part of the complexing agent first forms coordination with the metal ions, and then under the action of the coprecipitant and the remaining complexing agent, the first formed complex is used as the core to form an aggregate of primary particles with a hollow structure as shown in the embodiment; while Comparative Example 1 directly forms microparticles without a hollow structure.
[0108] (2) Preparation of positive electrode sheet: The lithium-rich manganese-based material prepared above, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30 mg / cm 2 After drying at 105℃, cold pressing, punching and welding the pole ears, the positive electrode sheet is obtained.
[0109] (3) Preparation of negative electrode sheet: Artificial graphite, conductive agent SP (conductive carbon black), thickener sodium carboxymethyl cellulose (CMC), and adhesive styrene butadiene rubber (SBR) are fully stirred and mixed in a proper amount of deionized water solvent at a weight ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode material layer, and then cut, slit, and weld the pole ears to obtain a negative electrode sheet.
[0110] (4) Preparation of lithium-ion batteries: The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil aluminum-plastic film, and the prepared electrolyte is injected into the dried bare battery cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, the preparation of the lithium battery of Comparative Example 1 is completed.
[0111] Comparative Example 2: Comparative Example 2 comprises the following steps: (1) Preparation of lithium-rich manganese-based materials: 75 g of manganese sulfate, 50 g of nickel sulfate and 42 g of lithium carbonate were mixed, 60 mL of isopropanol was added, and the mixture was ball-milled at 500 rpm / min for 8-12 h to obtain a mixture, which was then dried; The mixture was taken out and calcined at 550°C for 4 hours to obtain a lithium-rich manganese-based material.
[0112] (2) Preparation of positive electrode sheet: The lithium-rich manganese-based material prepared above, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30 mg / cm 2 After drying at 105℃, cold pressing, punching and welding the pole ears, the positive electrode sheet is obtained.
[0113] (3) Preparation of negative electrode sheet: Artificial graphite, conductive agent SP (conductive carbon black), thickener sodium carboxymethyl cellulose (CMC), and adhesive styrene butadiene rubber (SBR) are fully stirred and mixed in a proper amount of deionized water solvent at a weight ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode material layer, and then cut, slit, and weld the pole ears to obtain a negative electrode sheet.
[0114] (4) Preparation of lithium-ion batteries: The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil aluminum-plastic film, and the above-prepared electrolyte is injected into the dried bare battery cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, the preparation of the lithium battery of Comparative Example 2 is completed.
[0115] Electrochemical testing: Capacity retention test: The capacity retention rate test of Examples 1-7 and Comparative Examples 1-2, i.e., the cycle test, is performed at room temperature. The battery is charged to 4.2V with a 1C constant current, then charged to 0.05C with a constant voltage, left for 30 minutes, and then discharged to 2.5V with a 1C constant current, then left for 30 minutes. The above steps are repeated, and the battery discharge capacity Cn is recorded each time. The initial capacity of the battery is recorded as C0. The battery capacity after repeating the above steps for 300 cycles of charge and discharge is C300. The battery capacity retention rate for 300 weeks is calculated by the formula = C300 / C0*100%.
[0116] 1C discharge specific capacity test at 25℃: The 1C discharge specific capacity test was performed on Examples 1-7 and Comparative Examples 1-2. The lithium-ion battery was placed in a 25°C thermostat for 12 hours; then CC-CV charged to 4.95 V at 1 / 3 C, with a cutoff current of 0.05C; after standing for 10 minutes, 1 / 3C discharged to 3.5 V; the above steps were repeated 3 times; then 1C CC-CV charged to 4.95 V, with a cutoff current of 0.05C, and stood for 10 minutes; then 1C discharged to 3.5V, stood for 10 minutes, and the first 1C discharge capacity was taken as 1C 初始放电比容量 .
[0117] The results of the above electrochemical tests are shown in Table 1 below: Table 1
[0118] By comparing the electrochemical performance of Examples 1, 4-6, Comparative Examples 1-2 and Examples 2-3, combined with Figure 1-3 It can be seen that only when the lithium-rich manganese-based material is prepared, the following conditions are met: "First, add 55%-65% of the total mass of the complexing agent at room temperature, then stir for 15-30 minutes, then heat to 50°C-55°C, then add the aqueous solution of the coprecipitant and the remaining complexing agent, and then stir for 25-45 minutes" to obtain the following Figure 1 Or the aggregates obtained by aggregation of primary particles as shown in 2, which are ellipsoidal particles or spherical particles with a hollow structure or a hollow structure with a microcore, and the wall thickness of the ellipsoidal particles or spherical particles is 0.33-0.83μm, and the diameter of the inner wall is 0.43-1.1μm; it not only has higher capacity and voltage characteristics, but also has excellent capacity retention rate.
[0119] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the disclosure disclosed herein. The present disclosure is intended to cover any variations, uses or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises a lithium-rich manganese-based material, and the lithium-rich manganese-based material is an aggregate of primary particles; The minor axis length of the primary particle is selected from 190-310 nm, and the major axis length of the primary particle is selected from 400-660 nm; The D90 particle size of the aggregate is selected from 3.75-5.75 μm, and; Based on the total mass of the lithium-rich manganese-based material, the mass percentage of the lithium element in the lithium-rich manganese-based material is selected from 7.0%-10.0%, and the mass percentage of the manganese element in the lithium-rich manganese-based material is selected from 30.5%-37.5%.
2. The positive electrode material according to claim 1, characterized in that The lithium-rich manganese-based material further comprises nickel element. Based on the total mass of the lithium-rich manganese-based material, the mass percentage of the nickel element in the lithium-rich manganese-based material is selected from 21.3% to 27.3%.
3. The positive electrode material according to claim 2, characterized in that Based on the total mass of the lithium-rich manganese-based material, the percentage content of the sum of the mass of the nickel element and the mass of the manganese element in the lithium-rich manganese-based material is selected from 54.85% to 61.35%.
4. The positive electrode material according to claim 1, characterized in that The D50 particle size of the aggregates is selected from 2.25-3.50 μm.
5. The positive electrode material according to claim 1, characterized in that The D10 particle size of the aggregates is selected from 1.5-2.25 μm.
6. The positive electrode material according to any one of claims 1 to 5, characterized in that The lithium-rich manganese-based material is prepared by the following steps: Step 1: dissolving manganese salt and nickel salt in water, adding an aqueous solution of a complexing agent and a coprecipitant under stirring, then heating to 65°C-75°C, continuing stirring for 2-5 hours, and obtaining a precursor after aging; Step 2: Mechanically mixing the precursor and the lithium salt to obtain a mixture; Step 3: calcining the mixture at 450°C-600°C for 3-5h to obtain the lithium-rich manganese-based material.
7. The positive electrode material according to claim 6, characterized in that Step 1 comprises: dissolving manganese salt and nickel salt in water, adding 55%-65% of the total mass of the complexing agent at room temperature under stirring, stirring for 15-30 minutes, heating to 50°C-55°C, adding an aqueous solution of a coprecipitant and the remaining complexing agent, stirring for 25-45 minutes, further heating to 65°C-75°C, continuing stirring for 2-5 hours, and obtaining a precursor after aging.
8. The positive electrode material according to claim 6, characterized in that Steps 1 to 3 meet at least one of the following conditions: The manganese salt is selected from manganese sulfate; The nickel salt is selected from nickel sulfate; The complexing agent is selected from ammonia water; The coprecipitant is selected from at least one of sodium hydroxide, ammonium bicarbonate, sodium bicarbonate, ammonium oxalate and sodium oxalate; The lithium salt is selected from lithium carbonate; In step 1, the stirring rate is selected from 3000-3800 r / min.
9. A positive electrode sheet, characterized in that: The positive electrode plate comprises a positive electrode current collector and a positive electrode material layer coated on the positive electrode current collector, wherein the positive electrode material layer comprises the positive electrode material according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises a negative electrode plate, an electrolyte, a separator and the positive electrode plate according to claim 9.
Citation Information
Patent Citations
Rich-lithium-manganese-based cathode material used for lithium ion battery of hollow structure and preparation method thereof
CN104953110A
Preparation method of lithium-rich manganese-based positive electrode material with hollow structure
CN105977462A
Lithium-rich manganese-based precursor, preparation method thereof and lithium-rich manganese-based positive electrode material
CN109704415A
Preparation method of lithium-rich manganese-based positive electrode material
CN111640931A
Electrolyte solvents and methods for lithium meta and lithium ion batteries
WO2023069740A1